Patterns of Failure After Definitive Treatment of T4a Larynx Cancer. (August 2022) - Voora, Rohith S.; Panuganti, Bharat A.; Flagg, Mitchell; Nelson, Tyler; Kotha, Nikhil V.; Qiao, Edmund M.; Qian, Alexander S.; Kumar, Abhishek; Stewart, Tyler F.; Rose, Brent; Califano, Joseph; Weissbrod, Philip A.; et al.
Objective: Recurrence is known to predict laryngeal squamous cell cancer (LSCC) survival. Recurrence patterns in T4a LSCC are poorly characterized and represent a possible explanation for observed survival discrepancies by treatment rendered. Study Design: Retrospective database review. Setting: Veterans Affairs national database. Methods: Patients with T4a LSCC between 2000 and 2017 were identified and stratified by treatment (chemoradiotherapy [CRT] vs total laryngectomy + neck dissection + adjuvant therapy [surgical]). Primary outcomes were locoregional and distant recurrence. Secondary outcomes of overall mortality, larynx cancer mortality, and noncancer mortality were evaluated in Cox and Fine-Gray models. Results: A total of 1043 patients had comparable baseline demographics: 438 in the CRT group and 605 in the surgical group. Patients undergoing CRT had higher proportions of node positivity (64.6% vs 53.1%, P < .001). Locoregional and distant recurrence were less common in the surgical group (23.0% vs 37.2%, P < .001; 6.8% vs 13.3%, P < .001, respectively); however, distant metastatic rates did not differ within the N0 subgroup ( P = .722). On multivariable regression, surgery demonstrated favorable locoregional recurrence (hazard ratio [HR], 0.49; 95% CI, 0.39-0.62; P < .001), distant recurrence (HR, 0.47; 95% CI, 0.31-0.71; P < .001), overall mortality (HR, 0.75; 95% CI, 0.64-0.87; P < .001), and larynx cancer mortality (HR, 0.69; 95% CI, 0.56-0.85; P < .001). Conclusion: T4a LSCC survival discrepancies between surgical and nonsurgical treatment are influenced by varying recurrence behaviors. Surgery was associated with superior disease control and improved survival. Beyond the known benefit in locoregional control with surgery, there may be a protective effect on distant recurrence that depends on regional disease burden.